PERANAN PENARI PEREMPUAN DAN LAKI-LAKI DALAM PERTUNJUKAN TARI TAUH - Ahmad Damhuri; Darmawati Darmawati; Indra Yuda (SENDRATASIK UNP, 2013)
Abstract The article aimed at revealing the roles of female and male dancers in Tauh dance. The research used qualitative method. The data was descriptive obtained from observation, interview, and library research. The data was ethnography. The research showed that the role of female dancers was as the ones who were controlled by the male dancers and as the dancing partners. Moreover, the role of male dancers was as the leaders and as the one who controlled during the dancing. Male dancers moved more compared to that done by the female dancers. It indicated that in Tauh dance male dancers dominated more. Although male dancers were more dominant, the role of female dancers was important still. Therefore, in Tauh dance, male and female  dancers could not be separated each other. Kata kunci:        PenariPerempuan, Penari laki-laki, peran dan tari Tauh.